Stabilization Analysis of Clay Soil Using Xanthan Gum Additive - Rashita, Rani Ayu; Wulandari, Sri (Jurnal Teknik Sipil, 2025)
Effects of Xanthan gum Addition As A Stabilization Material On Clay Soil Parameters In Consolidation And Direct Shear Tests. The effect of the addition of a supplementary material called XG to the clay soil of Kabupaten Cirebon, West Java is investigated in this study. The study shall analyse the effects of Xg addition on clay soil's stability by means of consolidation and directly shear tests with a view to determining the proportion of XGT compound that is capable of stabilising soils. The results of the study indicate that the addition of XG to clayey soil successfully increased the CBR (California Bearing Ratio) value of the soil. With a cure interval of 28 days, the optimum percentage of XG addition has been found at 1.5% and resulted in CBR value values that are higher than those obtained by improving soil quality from poor to good. Moreover, the plasticity index of soil has increased as a result of adding XG. As the number of XG additions and treatment times rose, the plasticity index decreased. At the percentage of 1.5% XG addition with a 28-day curing period, the clayey soil fell into the medium plasticity category, reducing its potential for swelling. A 1.5% XG addition with a 28 day curing period has been the optimal percentage. At this percentage, the cohesion value of the soil reached its highest point, indicating an enhancement in the stability of the clayey soil. The knowledge gained from this research will be invaluable in the use of XG as an additive for clay soil stabilisation.